Methane Purification Using PVC Membrane: Preparation, Characterization and Performance Study - Sunarti, Abd Rahman; Raj, Roshan; Sureena, Abdullah; Siti Noraishah, Ismail; Wan Zulaisa Amira, Wan Jusoh (IJRTEM, 2017)
Methane (CH4) gas stands as one of the most prevalent gaseous in the air. Global methane emissions from landfill are estimated to be between 30 and 70 million tonnes each year. Methane originating from landfill is vastly found in developed and populated countries, where the levels of waste tend to be the highest. A study was done at Kampung Sg. Ikan Landfill in Kuala Terengganu, Malaysia. In this study, wastes were segregated according to specific types of wastes, such as 3D plastics (bottles), 2D plastic (food wrappers), glasses, food wastes and so on. From this study, it is found that food waste contributes the highest collection of waste for the past three weeks of segregation activities in the landfill. The data and studies from the landfill motivated a method was needed to separate gas from wastes using a cheap and effective polymer and hence, usage of PVC was used to separate CH4 gas from the CO2/CH4 mixture. The PVC membrane is produced by the combination of Polyvinyl Chloride (PVC) and N-Methyl-2-pyrrolidone, (NMP) via dry/wet phase inversion technique. The production of PVC membrane is expected to improve the characteristics of the polymeric membrane, such as the permeability, selectivity and the pore size. PVC is introduced with ratio of NMP (solvent): PVC, 82:18, 80:20, 77:23, and 75:25. This ratio enables the desired selectivity and permeability of CO2/CH4 gas separation. The PVC membrane with composition 77:23 was the highest performance in terms of selectivity at 2 bars. The SEM images of the surface morphology were included with the pore diameter ranging from 9.87µm to 28.7µm.